Complexity scales and licensing in phonology - Cyran, Eugeniusz (Studies in generative grammar, 2010)
This book is an attempt to demonstrate that the basic principles of phonological organization boil down to the interaction between the strength of nuclei as licensers of phonological structure and various non-rerankable scales of complexity occurring at different levels of phonological representation. The licensing relation between nuclei and the preceding onsets on the one hand, and governing relations between consonants, which are to a great extent determined by their internal melodic structure, allow us to view the phonological representation as a self-organizing system, which is able to pr.